FL listening motivation, interest, linguistic self-confidence, and overall proficiency: A complete double mediation model. (August 2022) - Tsang, Art
Abstract: Unlike reading motivation, listening motivation has largely been neglected by researchers, teachers, and learners. As one of the only two channels for receiving language input (the other being reading), listening is a very important first step for developing FL proficiency. The present study examined the interrelationships between three predictors (FL listening motivation, interest, and linguistic self-confidence), and an outcome (overall proficiency). One hundred and eleven primary 3–4 English-as-a-foreign-language children in Hong Kong completed a questionnaire and proficiency tests. The findings showed that all four variables were rather strongly inter-correlated. However, the path analysis revealed that the only significant relationship was a complete double mediation route (motivation→interest→confidence→proficiency). The study highlights the importance of listening motivation, furthers our understanding of its relationship with FL interest and confidence, and casts light on the mechanism of how it relates to overall proficiency via two mediators. Theoretical and pedagogical implications are discussed.